The Pathways to Homelessness in the Post-Soviet Context. Issue 45 (8th August 2019) - Sadzaglishvili, Shorena; Kalandadze, Tinatin
Abstract: Homelessness is a complex problem, resulting from a combination of housing and social exclusion processes. This paper discusses some theoretical discourses regarding understanding homelessness and the major factors contributing to homelessness (rooflessness) in the post-soviet country of Georgia. "Roofless" people are the most vulnerable group who need special attention while currently there is no national strategy on homelessness in place. Mixed methods were used to study homeless people living in a special shelter in Tbilisi. In total, 70 homeless (mean age = 48, male – 64%, female – 36%) were interviewed by semi-structural questionnaire. The results showed that a structural factor—unemployment (90%) was the major cause of homelessness. Moreover, almost half of the beneficiaries of emergency shelters need assistance in finding jobs even though they have high academic or professional education. In contrast to European roofless people who have multiple and serious support needs and problems (mental health, drag addiction, chronic homelessness), the majority of interviewed roofless people in Georgia are with less burdened life stories and can be more easily rehabilitated in the case of timely intervention, accommodation, and the proper national strategy on homelessness. Some recommendations for alleviating social segregation of homeless people are highlighted.